Identification of differentially expressed genes and signalling pathways in the ovary of higher and lower laying ducks. Issue 6 (1st November 2020) - Sun, Y.; Wu, Q.; Pan, J.; Li, T.; Liu, L.; Chen, D.; Zhang, X.; Chen, H.; Li, Y.; Lin, R.
ABSTRACT: 1. Ovarian transcriptomic profiling between birds showing high egg number (HEN) and birds of low egg number (LEN) in Longyan Shan-ma ducks at 71 weeks of age was carried out using Illumina Hiseq 2500 technology. 2. A total of 343 differentially expressed genes (DEGs, 269 upregulated and 74 downregulated) were identified between HEN and LEN ovaries. These DEGs were enriched in 30 Gene Ontology terms. Pathway functional analysis found that the DEGs were enriched in 10 metabolic pathways (P < 0.05), one of which was regulation of the actin cytoskeleton pathway ( Q < 0.05). 3. Three integrin family genes, ITGB2, ITGB5 and ITGA8 were differentially expressed in the RNA-seq and qPCR experiments. 4. The DEGs and signalling pathways identified in ovarian tissue in this study provide new insights into high egg production in Longyan Shan-ma duck.